Multi‐omics analysis points to altered platelet functions in severe food‐associated respiratory allergy. Issue 11 (9th August 2018) - Obeso, David; Mera‐Berriatua, Leticia; Rodríguez‐Coira, Juan; Rosace, Domenico; Fernández, Paloma; Martín‐Antoniano, Isabel Adoración; Santaolalla, Marcela; Marco Martín, Guadalupe; Chivato, Tomás; Fernández‐Rivas, Montserrat; Ramos, Tania; Blanco, Carlos; et al.
Abstract: Background: Prevalence and severity of allergic diseases have increased worldwide. To date, respiratory allergy phenotypes are not fully characterized and, along with inflammation progression, treatment is increasingly complex and expensive. Profilin sensitization constitutes a good model to study the progression of allergic inflammation. Our aim was to identify the underlying mechanisms and the associated biomarkers of this progression, focusing on severe phenotypes, using transcriptomics and metabolomics. Methods: Twenty‐five subjects were included in the study. Plasma samples were analyzed using gas and liquid chromatography coupled to mass spectrometry (GC‐MS and LC‐MS, respectively). Individuals were classified in four groups—"nonallergic, " "mild, " "moderate, " and "severe"—based on their clinical history, their response to an oral challenge test with profilin, and after a refinement using a mathematical metabolomic model. PBMCs were used for microarray analysis. Results: We found a set of transcripts and metabolites that were specific for the "severe" phenotype. By metabolomics, a decrease in carbohydrates and pyruvate and an increase in lactate were detected, suggesting aerobic glycolysis. Other metabolites were incremented in "severe" group: lysophospholipids, sphingosine‐1‐phosphate, sphinganine‐1‐phosphate, and lauric, myristic, palmitic, and oleic fatty acids. On the other hand, carnitines were decreased along severity. Significant transcripts in the "severe" group were found to be downregulated and were associated with platelet functions, protein synthesis, histone modification, and fatty acid metabolism. Conclusion: We have found evidence that points to the association of severe allergic inflammation with platelet functions alteration, together with reduced protein synthesis, and switch of immune cells to aerobic glycolysis. Abstract : Altered energy metabolism is connected to the immune cell activation. Sphingolipid metabolism variations and downregulation of platelet‐related transcripts in severe allergic patients point to an alteration of platelet functions. Multiple lipid membrane mediators including lysophosphatidylcholines (LPC), lysophosphoserines (LPS), and lysophosphoetanolamines (LPE) were found increased in severe allergic patients.